(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the challenges and opportunities in implementing customer-oriented quality management in Islamic education institutions, focusing on the balance between tradition and innovation. Using a quantitative approach, a survey was conducted among 500 respondents from various Islamic education institutions in Indonesia, including madrasah, pesantren and Islamic schools. Data were obtained through a questionnaire designed to measure respondents’ views on education quality management and its influence on education quality. The findings revealed that although most respondents were satisfied with education quality, there was an imbalance between preserving traditional values and adopting technological innovations. This gap is caused by limited resources, funding constraints and resistance to change. This research contributes to updating perspectives on quality management in Islamic education by emphasizing the integration of tradition and innovation to improve customer satisfaction. However, this research is limited by its scope and methodology.